1986
DOI: 10.1016/0304-3959(86)90171-5
|View full text |Cite
|
Sign up to set email alerts
|

Psychosomatic aspects of chronic pain: a new way of description based on MMPI item analysis

Abstract: Certain psychic structures which are represented in special configurations of MMPI scale values--the 'neurotic triad' and the 'conversion V'--are said to be typical of chronic pain patients. But considering the problems of reliability and validity of MMPI scales and new theoretical reflections regarding psychosomatic disorders, the diagnostic information given by these scale-based descriptions seems to be low. The present study examines the MMPI patterns of patients suffering from chronic headaches (N = 45) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

1989
1989
2005
2005

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 15 publications
0
16
0
1
Order By: Relevance
“…Some studies reported that migraine patients are overcontrolled in their behaviour and present personality traits that lead others to regard them as nice and agreeable people [16]. Other studies [24][25][26] suggested that migraine patients do not have a great deal of anger and/or suppressed anger, and if it is present, it is probably an unconscious defence mechanism; tension-type headache patients are more openly hostile and consciously troubled. Anger is a feeling that may be prone to denial because of social and moral norms, and in some cases, pain sufferers could have the tendency to deny angry feelings and aggressiveness [1].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported that migraine patients are overcontrolled in their behaviour and present personality traits that lead others to regard them as nice and agreeable people [16]. Other studies [24][25][26] suggested that migraine patients do not have a great deal of anger and/or suppressed anger, and if it is present, it is probably an unconscious defence mechanism; tension-type headache patients are more openly hostile and consciously troubled. Anger is a feeling that may be prone to denial because of social and moral norms, and in some cases, pain sufferers could have the tendency to deny angry feelings and aggressiveness [1].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they were associated with an inability to express emotional conflict and anger [15,[18][19][20][21][22], Greenberg and O'Neill [20] further documented that this emotional suppression or alexithymic characteristic was tied to somatic symptoms including migraine head aches. Studies support the association between anger and anxiety suppression and emotionally laden dreams [9,11,30], Early studies and some current research supported a firm relationship between migraines and personality traits such as obsessive compulsion associated with per fectionism [1,[15][16][17], Frustration and anxiety were asso ciated with attempts to meet self-imposed expectations, as migraineurs overextended themselves [15].…”
Section: Discussionmentioning
confidence: 99%
“…Migraine headaches were associated with personality traits such as obsessive compulsion associated with perfectionism [1,[15][16][17]. Migraineurs were found to be excessive in self-control complicated by the inability to express frustration, anger or hostility [15,[18][19][20][21][22], This pattern was often associated with childhood experiences [1,15,18,[21][22][23][24][25], Research supported a relationship between migraine onset and the occurrence of psychologically important events [26], Moreover, Lance [13] explained that neuro vascular systems were vulnerable to an individual's re sponse to stress, and in migraineurs it may 'reduce cere bral activity and blood supply' [p. 79], In this regard, stress precipitated serotonin reduction related to vasocon striction and pain perception in the brain [2; Joyce, pers. commun., March 5, 1993].…”
Section: Migraine Backgroundmentioning
confidence: 99%
“…Despite some criticisms about the adequacy and risks of misinterpretation of some scales [15,16], the MMPI has been widely used to investigate the personality of patients with headache and other types of facial pain. In migraine The MMPI-2 in women with headache or facial pain.…”
Section: Introductionmentioning
confidence: 99%
“…The Minnesota Multiphasic Personality Inventory (MMPI) [1] is probably the most widely used of such instruments [2][3][4][5][6][7][8][9][10][11][12]. Depending on the answers (truefalse) to a large number of questions, a score is given on 3 validity scales (L = lie, F = frequency, K = correction or defence) and on 10 clinical scales (Hs = hypochondria, D = depression, Hy = hysteria, Pd = psychopathological deviation, Mf = masculinity-femininity, Pa = paranoia, Pt = psychasthenia, Sc = schizophrenia, Ma = hypomania, Si = social introversion).Four types of MMPI typologies were proposed based on some characterizing algorithms [13,14]: one type with the "conversive V" profile (with Hs and Hy scores above normal and D being at least 10 points lower); a second "depressed" type, with elevation of the neurotic triad (HS, D, Hy) and of depression in particular, with no other scale being consistently elevated; a third type of "emotionally overwhelmed" patients with scale elevation of the neurotic triad and several other scales; and lastly a fourth type (the "coper") with a normal profile.Despite some criticisms about the adequacy and risks of misinterpretation of some scales [15,16], the MMPI has been widely used to investigate the personality of patients with headache and other types of facial pain. In migraine The MMPI-2 in women with headache or facial pain.…”
mentioning
confidence: 99%